A Voltage Controller in Photo-Voltaic System with Battery Storage for Stand-Alone Applications - Ganesh Dharmireddy; Moorthi S; Sudheer Hanumanthakari (Institute of Advanced Engineering and Science, 2012)
This paper proposes the new voltage controller in photo-voltaic system for Stand-Alone Applications with battery energy storage. The output of the PV array is unregulated DC supply due to change in weather conditions. The maximum power is tracked with respect to temperature and irradiance levels by using DC-DC converter. The perturbation and observes algorithm is applied for maximum power point tracking (MPPT) purpose. This algorithm is selected due to its ability to withstand against any parameter variation and having high efficiency. The solar cell array powers the steady state energy and the battery compensates the dynamic energy in the system. The aim of the control strategy is to control the SEPIC converter and bi-direction DC-DC converter to operate in suitable modes according to the condition of solar cell and battery, so as to coordinate the two sources of solar cell and battery supplying power and ensure the system operates with high efficiency and behaviors with good dynamic performance. The output of DC-DC converter is converted to AC voltage by using inverter. The AC output voltage and frequency are regulated. A closed loop voltage control for inverter is done by using unipolar sine wave pulse width modulation (SPWM). The regulated AC voltage is fed to AC standalone loads or grid integration. The overall system is designed, developed and validated by using MATLAB-SIMULINK. The simulation results demonstrate the effective working of MPPT algorithm, control strategy and voltage controller with SPWM technique for inverter in AC standalone load applications.DOI: http://dx.doi.org/10.11591/ijpeds.v2i1.127